2006
DOI: 10.1002/ijc.21885
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in Belarus and Ukraine after the Chernobyl accident

Abstract: An increase in breast cancer incidence has been reported in areas of Belarus and Ukraine contaminated by the Chernobyl accident and has become an issue of public concern. The authors carried out an ecological epidemiological study to describe the spatial and temporal trends in breast cancer incidence in the most contaminated regions of Belarus and Ukraine, and to evaluate whether increases seen since 1986 correlate to radiation exposure from the Chernobyl accident. The authors investigated the trends through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 19 publications
0
60
1
3
Order By: Relevance
“…A study of breast cancer incidence after the Chernobyl accident found an increased risk among women resident in the most contaminated districts (average cumulative whole body dose of 50 mSv) with an ERR of 1.2 (95% CI, 0.5, 2.3) in Belarus and 0.8 in Ukraine (95% CI: 0.1; 1.9). However, the limitations of ecologic studies require that this finding be interpreted with caution (Pukkala et al, 2006).…”
Section: Breast Cancer Incidence In the Techa River Cohort E Ostroumomentioning
confidence: 99%
See 1 more Smart Citation
“…A study of breast cancer incidence after the Chernobyl accident found an increased risk among women resident in the most contaminated districts (average cumulative whole body dose of 50 mSv) with an ERR of 1.2 (95% CI, 0.5, 2.3) in Belarus and 0.8 in Ukraine (95% CI: 0.1; 1.9). However, the limitations of ecologic studies require that this finding be interpreted with caution (Pukkala et al, 2006).…”
Section: Breast Cancer Incidence In the Techa River Cohort E Ostroumomentioning
confidence: 99%
“…Associations between cancer risks from low-dose occupational radiation exposure (Wang et al, 2002;Doody et al, 2006) or protracted low-to-moderate dose environmental radiation exposure (Bauer et al, 2005;Pukkala et al, 2006) have, however, been reported.…”
mentioning
confidence: 99%
“…The latency would fit better with a hypothesis of an effect of ionising radiation. 30 Studies have advocated either pelvic or whole abdominal radiotherapy for treatment of PFTC, but because of low efficacy and a high rate of serious complications this should no longer be used except for palliation of specific symptoms. 2,8,[31][32][33] The total doses used in the pelvic or total abdominal radiotherapy have ranged from 25 to 70 Gy (median 50.0 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…An increased incidence of breast cancer due to radiation exposure was observed in the atomic bomb survivors [236][237][238][239], and radiation-associated breast tumours were quite aggressive and associated with increased levels of genomic instability and higher histological grade in breast cancer [240]. Also up to 2-fold increase in breast cancer (both localised and metastatic diseases) following the Chernobyl accident in 1986 was estimated during the period 1997-2001 in the most contaminated districts (average cumulative dose of 40.0 mSv or more), whereby the increase appeared approximately 10 years after the accident, and it was highest among women who were younger at the time of exposure [241].…”
Section: Ionizing Radiationmentioning
confidence: 99%